2017
DOI: 10.1177/0194599817721153
|View full text |Cite
|
Sign up to set email alerts
|

CT Study of the Arytenoid Cartilage in Patients with Laryngeal Contact Granuloma

Abstract: Objective To explore high-resolution computed tomography (HRCT) characteristics of arytenoid cartilage in patients with laryngeal contact granuloma (LCG). Setting Tertiary hospitals. Study Design Individual case-control study. Methods HRCT scans were obtained before treatment from 42 patients with LCG. Similar scans were obtained from 50 patients with glottic laryngeal cancer or vocal cord leukoplakia without vocal process involvement. Results Forty-two male patients with LCG were enrolled in the study. There … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The presence of calcification may support the diagnosis of LCG, and this finding is consistent with our conclusion. 8 Limited studies have focused on the relationship between the extent of arytenoid cartilage calcification in LCG and the possible future recurrence of granulomas. A correlation of CT gray values in HU and biomechanical properties has been shown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of calcification may support the diagnosis of LCG, and this finding is consistent with our conclusion. 8 Limited studies have focused on the relationship between the extent of arytenoid cartilage calcification in LCG and the possible future recurrence of granulomas. A correlation of CT gray values in HU and biomechanical properties has been shown.…”
Section: Discussionmentioning
confidence: 99%
“…7 Similarly, Li et al recently found calcification on arytenoid cartilage in high-resolution computed tomography (HRCT) scans in 43 cases of idiopathic vocal process granuloma lesions (cases of intubation granuloma were excluded). 8 Thus, it may be important to evaluate the therapeutic strategy and prognosis of post-surgical recurrent LCG by investigating the morphological and histological characteristics of arytenoid cartilage calcification before surgery and calculating its severity.…”
Section: Introductionmentioning
confidence: 99%